GOVERNANCE OF TIDAL FLOOD MITIGATION IN DEMAK REGENCY: FISCAL CONSTRAINTS, INSTITUTIONAL FRAGMENTATION, AND THE NEED FOR A STRUCTURAL APPROACH - Muhammad Alip; Maria Ekowati (Media Inovasi Pendidikan dan Publikasi, 2026)
Tidal flooding that has occurred intensively in Demak Regency, particularly in the northern coastal area of Central Java covering Sayung, Karangtengah, Bonang, and Wedung Districts, has generated increasingly complex social, economic, and environmental impacts. This phenomenon is driven by sea level rise, land subsidence, coastal erosion, and land-use changes that increase the vulnerability of coastal areas to recurrent tidal inundation. Efforts to manage tidal flooding face several challenges, including limited fiscal capacity of local governments, fragmented authority across different levels of government, and the lack of optimal policy integration in coastal area management. This study aims to analyze the governance of tidal flood management in Demak Regency and to identify the need for a structural approach to support the effectiveness of mitigation efforts. This study employs a qualitative method with a descriptive approach. Data were collected through literature reviews, policy document analysis, government reports, previous research findings, and various relevant secondary data sources. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the problems and strategies related to tidal flood management in Demak Regency. The findings indicate that the governance of tidal flood management in Demak Regency still faces challenges related to inter-agency coordination, limited funding, and overlapping authorities. These conditions have hindered the implementation of effective and sustainable mitigation efforts. Therefore, a structural approach is required through the development of tidal flood control infrastructure, strengthening synergy among stakeholders, and increasing financial support from the central government. Such an approach is expected to improve governance effectiveness and enhance the resilience of Demak Regency’s coastal areas against tidal flood hazards.